the educational curriculum in the Maghreb region during the Al-Hammadid era A Study of Roles , Influe - leghrib, Ahlem; harouz, abdelghani (Journal of Social Sciences and Humanities, 2023)
This research paper examines the educational curriculum in the Maghreb region during the Al-Hammadid era (408-547AH/ 1018-1152 CE),It explores the foundations and methodological mechanisms of the Al-Hammadid educational system, which had a significant impact on the region, driving intellectual and cultural development. This young nation, built by the people of the region, shone as a hub of scientific and educational excellence, influenced by and influencing previous and contemporary educational models. The Al-Hammadid perspective in curriculum development transcended individual educators or educational institutions, reflecting a holistic vision for the state. Thus, the aim of this research paper is to shed light on the curriculum aspect of the educational system during the Al-Hammadid era. To achieve this goal, a descriptive historical approach was adopted, allowing for an in-depth understanding of the educational curriculum and its programs during the studied